2021
DOI: 10.1111/1748-8583.12410
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the linguistic markers of intuition in human resource (HR) practice

Abstract: Intuitions are judgements that arise automatically and non‐consciously. Recognising when intuitive judgements are being used and whether doing so is appropriate is an important skill both for HR practitioners and managers involved in human resource (HR) processes. Because ‘intuiting’ is involuntary and unconscious it is difficult to access, monitor and control, however people can access and articulate their intuitive judgements through the spoken/written word. Identifying ‘linguistic markers’ of intuitions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 98 publications
1
4
0
Order By: Relevance
“…Recent studies have successfully shown technology-based tools measure performance on divergent-thinking tasks (Acar & Runco, 2014; Beketayev & Runco, 2016; Dumas & Dunbar, 2014). The present study supports the assertion that automated forms of assessment provide the required speed and reliability (Sadler-Smith et al, 2021). Extending text-mining tools to reliable automated essay scoring is essential to provide teachers with efficient and effective means to assess compositions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Recent studies have successfully shown technology-based tools measure performance on divergent-thinking tasks (Acar & Runco, 2014; Beketayev & Runco, 2016; Dumas & Dunbar, 2014). The present study supports the assertion that automated forms of assessment provide the required speed and reliability (Sadler-Smith et al, 2021). Extending text-mining tools to reliable automated essay scoring is essential to provide teachers with efficient and effective means to assess compositions.…”
Section: Discussionsupporting
confidence: 88%
“…We used LIWC (Pennebaker et al, 2015) to obtain a word count for each essay, which it determined against an established dictionary that highlighted psychological phenomena. The original use of LIWC was to determine particular psychological characteristics from written texts but also had applications for academic and creative assessment (Sadler-Smith et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…It could have been sufficient to analyze Sinclair and Ashkanasy's construct, which is antecedent and similar to that of Dane and Pratt's, but Dane and Pratt's construct has been increasingly accepted in the field of management as the consensual definition; it is regarded as the most comprehensive and most referenced definition of intuition (Okoli et al, 2021): for example, Akinci and Sadler-Smith (2012, p. 115) wrote that, despite several studies flourishing throughout the years, Dane and Pratt's is the only "comprehensive, integrated account and testable research propositions". So the article has formed the basis of a number of subsequent influential literature reviews, conceptual contributions, and methodological and empirical works; drawing from it, scholars have differentiated intuition from related constructs (Hodgkinson et al, 2008(Hodgkinson et al, , 2009aSadler-Smith, 2010, 2015Salas et al, 2010;Blume and Covin, 2011;Akinci and Sadler-Smith, 2012, 2013, 2020Baldacchino, 2013Baldacchino, , 2019Baldacchino et al, 2015;Healey et al, 2015;Pratt and Crosina, 2016;Calabretta et al, 2017;Okoli et al, 2021;Sadler-Smith et al, 2021). In addition, the article has spread over psychology and neuroscience (Hodgkinson et al, 2008;Hogarth, 2010;Gore and Sadler-Smith, 2011;Hodgkinson and Healey, 2011;Ben-Soussan et al, 2020;Keck and Tang, 2020;Korteling and Toet, 2020;Li et al, 2020;Stephens et al, 2020;West et al, 2020;Muñoz-Cobos and Postigo-Zegarra, 2021;Reynolds et al, 2021;Yu et al, 2021;Zhang et al, 2021), as well as distant disciplinary domains, su...…”
Section: No Agreementmentioning
confidence: 99%
“…AI-enabled tools can be utilized to coordinate with candidates throughout the process. Another study (Sadler-Smith et al, 2022) utilized computerized text analysis to identify linguistic markers of intuition based on HR practices to determine what happens when they intuit. Generally, intuitions arise intentionally and automatically.…”
Section: Resultsmentioning
confidence: 99%